Pengaruh Lingkungan Kerja, Kepuasan Kerja dan Beban Kerja terhadap Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Provinsi Sumatera Barat - Dewirahmadanirwati, Dewirahmadanirwati; Manalu, Sri Rezeki (Lembaga Yasin AlSys, 2025)
Work environment, job satisfaction, and workload are factors believed to influence employee performance; however, several previous studies have shown inconsistent results, particularly in the public sector. This study aims to determine the effect of work environment, job satisfaction, and workload on employee performance at the Investment and Integrated One-Stop Service Agency (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu, DPMPTSP) of West Sumatra Province. The approach used is quantitative with primary data sources. The sampling technique applied is total sampling, involving 45 employee respondents. Data were collected through questionnaires, interviews, and observations, and then analyzed using SPSS version 25. The analysis stages include data quality tests (validity and reliability), classical assumption tests, multiple linear regression tests, and hypothesis testing (t-test). The results indicate that the work environment and workload have a positive and significant effect on employee performance, while job satisfaction does not have a significant effect. These findings provide empirical contributions to the development of human resource management in the public sector, particularly in improving performance through the optimal management of work environment and workload.